The involvement of a regucalcin in suppressing hemocyte apoptosis in Pacific oyster Crassostrea gigas. Issue 103 (August 2020) - Lian, Xingye; Huang, Shu; Han, Shuo; Yi, Qilin; Wang, Weilin; Sun, Jiejie; Wang, Lingling; Song, Linsheng
Abstract: Regucalcin (RGN), also known as senescence marker protein-30 (SMP30), plays a vital role in the regulation of Ca 2+ homeostasis. In the present study, a regucalcin (designated as Cg RGN) was identified from Pacific oyster Crassostrea gigas . The complete cDNA sequence of Cg RGN was of 1059 bp, containing an open reading frame of 933 bp which encoded a protein of 310 amino acids. The deduced amino acid sequence of Cg RGN shared similarity with other RGNs from the genome of C. gigas as well as other species. The mRNA transcripts of Cg RGN were universally detected in all tested tissues, with higher level in hepatopancreas, labial palp, and gills. The relative expression level of Cg RGN in hemocytes was significantly up-regulated ( p  < 0.05) at 3, 12, 72, and 96 h after the stimulation of lipopolysaccharide (LPS). After Cg RGN expression was interfered by specific Cg RGN-dsRNA, the hemocytes apoptosis rate increased dramatically at 12 h post LPS stimulation (1.56 fold, p  < 0.01), compared to the control group. The caspase-3 activity in hemocytes and NO concentration in hemolymph increased significantly ( p  < 0.05) in ds Cg RGN injection oysters. These results collectively indicated that Cg RGN could suppress LPS-induced apoptosis and be involved in the immune response of oysters. Highlights: A RGN was identified from Pacific oyster Crassostrea gigas ( Cg RGN). The mRNA transcripts of Cg RGN were up-regulated after LPS stimulation. Cg RGN could inhibit the apoptotic rate of oyster hemocytes. Cg RGN might suppress apoptosis by regulating caspase-3 activity and NO production.